BENIGN IDIOPATHIC INFANTILE MASTURBATION: A CASE REPORT OF SEIZURE MIMICKING IN A 3-YEAR-OLD INFANT - Retno Jayantri Ketaren; Jacqueline Tasha Margono (MNJ (Malang Neurology Journal), 2023)
Background: Benign idiopathic infantile masturbation (infantile dyskinesia) or also known as gratification disorder is a rare abnormal paroxysmal movement disorder that occurs in children between 3 months and 3 years old. This disorder is characterized by self-stimulation of the genitalia and associated with unusual posturing and movements. Therefore, it could mimic as seizure.2 The diagnosis of this disorder may be perplexing and scarcely reported. Case Findings: We reported a 3 years old infant with abnormal behavior and posturing with rocking and thrusting movements accompanied by erection and clear secretion from his penis. The episodes were described as hip and knee flexion towards the abdomen, plantar flexion with flexion of the toes, extension of the elbows, clenched fists, and this behavior always occurred while lying in bed. Physical and neurological examination showed normal results. The electroencephalogram (EEG) was within normal limits hence done to exclude seizure as diagnosis. Parents were then educated and the child now does not show any previous behavior. Conclusion: Benign infantile masturbation is a harmless behavior that is scarcely reported in journals and commonly mistaken as seizure. It presents with typical clinical characteristics and commonly found in females. However, our case report showed that this disorder may also be found in male with additional characteristics such as erection and clear secretion from the penis. To date, there is no exact treatment that could alleviate the symptom other than patient education. Keywords: Gratification Disorder, Benign Infantile Masturbation.